Answer:
13/6
Step-by-step explanation:
1 Simplify \sqrt{8}
8
to 2\sqrt{2}2
2
.
\frac{2}{6\times 2\sqrt{2}}\sqrt{2}-(-\frac{18}{\sqrt{81}})
6×2
2
2
2
−(−
81
18
)
2 Simplify 6\times 2\sqrt{2}6×2
2
to 12\sqrt{2}12
2
.
\frac{2}{12\sqrt{2}}\sqrt{2}-(-\frac{18}{\sqrt{81}})
12
2
2
2
−(−
81
18
)
3 Since 9\times 9=819×9=81, the square root of 8181 is 99.
\frac{2}{12\sqrt{2}}\sqrt{2}-(-\frac{18}{9})
12
2
2
2
−(−
9
18
)
4 Simplify \frac{18}{9}
9
18
to 22.
\frac{2}{12\sqrt{2}}\sqrt{2}-(-2)
12
2
2
2
−(−2)
5 Rationalize the denominator: \frac{2}{12\sqrt{2}} \cdot \frac{\sqrt{2}}{\sqrt{2}}=\frac{2\sqrt{2}}{12\times 2}
12
2
2
⋅
2
2
=
12×2
2
2
.
\frac{2\sqrt{2}}{12\times 2}\sqrt{2}-(-2)
12×2
2
2
2
−(−2)
6 Simplify 12\times 212×2 to 2424.
\frac{2\sqrt{2}}{24}\sqrt{2}-(-2)
24
2
2
2
−(−2)
7 Simplify \frac{2\sqrt{2}}{24}
24
2
2
to \frac{\sqrt{2}}{12}
12
2
.
\frac{\sqrt{2}}{12}\sqrt{2}-(-2)
12
2
2
−(−2)
8 Use this rule: \frac{a}{b} \times c=\frac{ac}{b}
b
a
×c=
b
ac
.
\frac{\sqrt{2}\sqrt{2}}{12}-(-2)
12
2
2
−(−2)
9 Simplify \sqrt{2}\sqrt{2}
2
2
to \sqrt{4}
4
.
\frac{\sqrt{4}}{12}-(-2)
12
4
−(−2)
10 Since 2\times 2=42×2=4, the square root of 44 is 22.
\frac{2}{12}-(-2)
12
2
−(−2)
11 Simplify \frac{2}{12}
12
2
to \frac{1}{6}
6
1
.
\frac{1}{6}-(-2)
6
1
−(−2)
12 Remove parentheses.
\frac{1}{6}+2
6
1
+2
13 Simplify.
\frac{13}{6}
6
13
Done
Answer:
8,613
Step-by-step explanation:
Check the picture below.
notice that the car exits the northbound highway, and whilst going at 50mph for 1.5 hours, that simply means going for 75 miles.
make sure your calculator is in Degree mode.
Answer:
one gadget costs $15.80
Step-by-step explanation:
Let w = cost of one widget
Let g = cost of one gadget
Given:
- Five widgets and three gadgets cost $109. 90
⇒ 5w + 3g = 109.9
Given:
- One widget and four gadgets cost $75. 70
⇒ w + 4g = 75.7
Rewrite w + 4g = 75.7 to make w the subject:
⇒ w = 75.7 - 4g
Substitute into 5w + 3g = 109.9 and solve for g:
⇒ 5(75.7 - 4g) + 3g = 109.9
⇒ 378.5 - 20g + 3g = 109.9
⇒ 378.5 - 109.9 = 20g - 3g
⇒ 268.6 = 17g
⇒ g = 15.8
Therefore, one gadget costs $15.80
To find the cost of one widget, substitute the found value for g into
w = 75.7 - 4g and solve for w:
⇒ w = 75.7 - 4(15.8)
⇒ w = 75.7 - 63.2
⇒ w = 12.5
Therefore, one widget costs $12.50
3, 6, 9, 12, 15, 18, 21, 24, 27, 30.